An effective metal-organic framework-based electrochemical non-enzymatic glucose sensor - Daud, A.D.; Lim, H.N.; Ibrahim, I.; Endot, N.A.; Gowthaman, N.S.K.; Jiang, Z.T.; Cordova, Kyle E. (Elsevier, 2022)
Herein, we report a non-enzymatic glucose sensor based on a metal-organic framework (MOF) as alternative approach for long-term glucose monitoring. Specifically, nickel-based MOFs were solvothermally synthesized using either 2-amino-1,4-benzenedicarboxylic acid (BDC-NH2) or 2-hydroxy-1,4-benzenedicarboxylic acid (H2BDC-OH), both of which were characterized by different physicochemical techniques. The electrochemical performance of both electrodes towards glucose sensing was investigated and Ni-BDC-NH2 exhibited a significantly better electrocatalytic behaviour towards oxidation of glucose than bare Ni-BDC or Ni-BDC-OH in an alkaline media. This was attributed to a favourable multi-layered sheet-like structure that allowed diffusion for entrapment of glucose and the incorporation of –NH2 functional groups attached to the BDC linker which, were responsible for electrochemical adsorption of glucose molecules. Ni-BDC-NH2 displayed a lower detection limit (3.82 μM), higher stability (>180 days), and remarkable sensitivity (308 μA mM−1 cm−2). Additionally, a molecular sieve effect for Ni-BDC-NH2 led to a noteworthy anti-interference ability and the sensor displays a fast response time of 5.4 s towards glucose detection. These results indicate that the as-synthesized non-enzymatic glucose sensor operates with a longer lifetime and is viable for use as an intensive monitoring system.